G154(P) Transition of patients with sickle cell disease – how can we help? results of a survey of adolescents recently transferred to adult services. (27th April 2015) - Chanchlani, N; Harewood, C; Hossain, U; Leigh, A
Abstract : Background: Recent reports suggest transition of young people with chronic diseases from paediatric to adult services is often untimely, ineffective, and poorly managed. Sickle cell disease (SCD) is typically diagnosed in childhood. Despite data reporting that rates of emergency admissions increase around the time of transition, few studies have reported experiences of patients undergoing transfer to adult services. Aim: We sought to survey adolescents with SCD who had recently transferred from paediatric to adult services in order to identify barriers to successful transition. Methods: Adolescents who had recently transferred from paediatric to adult services at a single site were identified. Patients were initially contacted by post with a letter and a copy of the validated Sickle Cell Disease Transition Questionnaire, assessing patients' self-reported illness, functional skills, and disease management efficacy. Non-responders were followed up by a phone-call and voice message after one and two months. Results: Thirteen adolescents were identified; six (46%) completed surveys. One was not receiving medical care in an adult setting and excluded. Four (80%) were aware of their haemoglobin type. The most common concerns regarding transfer to an adult care programme included unclear expectations [n = 4], ineffective communication [n = 4], and fear of being in a new environment [n = 3]. All those surveyed agreed that a dedicated transition programme would be useful to their health needs, and would assist in transferring care [n = 5], providing support [n = 4], and providing an opportunity to meet other adults with sickle cell disease [n = 2]. Participants varied in self-reported illness experiences, but four (80%) reported independently managing acute sickle and non-sickle disease medical problems before calling the doctor, except if severely unwell. Conclusion: Recently transitioned SCD patients placed a high importance on quality of information during transition and cultural independence, in particular from parents, during the transition of care from paediatric to adult services. Prior to implementation of a transition clinic, surveying users can help inform doctors and nurses of what to prioritise and how to effectively communicate relevant information.